Two new species of Paraneseuthia Franz (Coleoptera, Staphylinidae, Scydmaeninae) from West Malaysia - Jałoszyński, Paweł (Zootaxa, 2014)
Two new species of Paraneseuthia are described from peninsular Malaysia: P. joeparkeri sp. n. from Bukit Larut (Maxwell Hill) and P. titiwangsana sp. n. from the Genting Highlands. The new species are morphologically allied to species known so far only from Sumatra; they all share emarginate apex of the aedeagus bordered at each side by a subtriangular projection and a pair of setae. This is the first record of this eutheiine genus from the Malay Peninsula and extends the known diversity of Paraneseuthia species within the historical Sundaland area.